MRI approaches for neurovascular imaging - Dijkhuizen, Rick (Henry Stewart Talks, 2009)
Imaging neurovascular health and disease, Magnetic Resonance Imaging, Functional MRI, Bold MRI, Function MRI after cerebrovascular injury, MRI of blood-brain barrier permeability, Cellular MRI, Molecular MRI, MRI of neurovascular unit